Sava Transformation Chronicle (A) - Nenad Filipović (Mednarodno Inovativno Poslovanje)
This case study is part of a sequel of cases (from A to D) prepared to be used together in a course on Strategic Management (more in particular on topics related to Mergers and Acquisitions, Business Portfolio Management and Corporate Transformation). Due to the article length restrictions, parts B – D, as well as the case Teaching Note, will be published in a separate article. Please refer to the Teaching Note for more precise suggestions related to classroom use.